Deductive Teachers’ Perception using Inductive Instruction in Teaching English Grammar - Rismayanti, Luh Ayu; Utami, I.G.A.L.P.; Suprianti, G.A.P. (Journal of Education Reseach and Evaluation, 2021)
Learning English is essential for international students. English is an essential international language used to communicate with other people worldwide. The discussion of English cannot be separated from other aspects. Over the years, discussions of grammar have been debated and become an issue in learning English. However, there are still many students who have difficulty learning English. The purpose of this research is to analyze the perception of teachers, especially those who routinely use deductive reasoning, to the use of an inductive approach in teaching grammar. This research uses qualitative research with a case study design. In this study, the teacher's approach, especially the more routinely used deductive approach to learning approaches in teaching procedures. The research instruments used were observation, document analysis, and interview guidelines. Collecting data obtained through observation sheets, lesson plans analysis, and interviews. This study found that although English teachers generally prefer a deductive approach, it does not mean that they do not use an inductive approach at all. Findings of positive perceptions of deductive teachers towards inductive instruction in teaching grammar from the interview session.